Multi-Hazard Chain Reaction Initiated by the 2020 Meilong Debris Flow in the Dadu River, Southwest China - Ning, Lan; Hu, Kaiheng; Wang, Zhang; Luo, Hong; Qin, Haokun; Zhang, Xiaopeng; Liu, Shuang (Frontiers in Earth Science, 2022)
Delivery of large volumes of sediment by debris flows in a short time into rivers often initiates a hazardous chain reaction in alpine valleys. Predicting the Multi-hazard chain's evolution and intervening in its cascading effects by artificial countermeasures face major challenges due to variations in the spatial and temporal extent of controlling factors. On June 17, 2020, a rainstorm-induced debris flow event with a volume of 2.4×105 m3 occurred in the Meilong catchment, Danba County, Sichuan Province, Southwest China, which triggered a debris flow–outburst flood–landslide multi-hazard chain. Large amounts of soil and debris entered the Xiaojinchuan River and formed a barrier lake. The outburst flood and narrowed river flow eroded 2.76×106 m3 of old deposits at the foot of the Aniangzhai landslide, leading to its reactivation. Engineering measures, including dredging, rechanneling, and embankment construction, were implemented to prevent the hazard from spreading further. The deformation velocity and acceleration of the landslide decreased from a peak of 75 mm/h to 8.74 mm/h and a peak of 16.46 mm/h2 to 0.13 mm/h2 before and after the engineering, respectively, according to measurements of a ground-based monitoring radar. Without the engineering measures, the factor of safety of the landslide would be reduced to 0.93, and a larger landslide dam hazard would occur if the foot were eroded by more than 17 m. This case and its successful engineering demonstrate that artificial intervention measures are effective in halting the cascading process of natural hazards.